A discussion: comparison of demagnetization fields and depolarization fields. Issue 4 (27th December 2019) - Ai, Shu-Tao; Zhang, Shao-Yin; Cai, Yuan-Zhen
Abstract: The differences between demagnetization fields and depolarization fields were compared. The most fundamental reason is the existence of electric charges but the nonexistence of magnetic charges. For ferroics (ferromagnetics and ferroelectrics), the non-equilibrium thermodynamics of phase transitions was considered and the conclusion remains the same.